PERANCANGAN SISTEM PEMINJAMAN ALAT BENGKEL OTOMOTIF BERBASIS DIAGRAM USE CASE DAN AKTIVITAS UNTUK MENINGKATKAN EFISIENSI DAN TRANSPARANSI OPERASIONAL - Muhammad Fadly; Ovan Sunarto Pulu (Jurnal Ilmiah Teknik, 2025)
Efficient tool management in automotive workshops is often hindered by manual systems prone to errors, delays, and a lack of transparency. This study aims to design a digital tool borrowing system using use case and activity diagrams to enhance efficiency and accountability. The use case diagram maps the roles of borrowers, administrators, and technicians, while the activity diagram illustrates the detailed workflow, from tool availability checks to returns and damage reporting. The design results show that the system provides key features, such as automated tool availability checks, digital approvals, transaction recording, and damage reporting. The implementation of this system reduces borrowing process time, enhances transparency in tool management, and ensures tools are maintained in good condition. The proposed system not only improves the operational efficiency of workshops but also offers a better user experience. With potential integration of technologies such as the Internet of Things (IoT) and blockchain, the system can be further developed to enable real-time tool tracking and enhance data security.